Central Retinal Artery Occlusion Secondary To High Altitude Exposure - Diviyanshu Nadda; Jyoti Sheoran; Saurabh Sachar; Anurag Narula (Delhi Journal of Ophthalmology)
CRAO can be considered as an ocular analogue of stroke or an ocular equivalent of acute myocardial infarction. We present a case report of a 32-years-old serving soldier posted at high altitude area with no premorbidities who presented with symptoms of sudden painless loss of vision in the left eye (LE). Best-corrected visual acuity in the LE was PL+ with PR inaccurate. A relative afferent pupillary defect grade IV was observed in the LE. Ocular fundus examination of LE was suggestive of central retinal artery occlusion. Systemic evaluation revealed Steno occlusive disease of bilateral carotids L>R. Haematological investigations revealed increased haemoglobin. Raised haemoglobin due to long stay in high altitude area is tantamount to a sustained inflammatory state that results in endothelial dysfunction by causing hypercoagulable state culminating in small calibre vessel blockage.